Critical thinking; issues in nursing education and practice - Aagbedia, Clara Oniovokoyubu; Ogbe, Joseph (International Journal of Advanced Nursing Studies, 2013)
The emphasis on the use of the nursing process in both nursing education and clinical practice would lead one to expect that the process of critical thinking is well understood and applied in nursing situation. But this is not the case. There is a substantial body of evidence to show that tasks, ward routines and rituals and procedures socialization of neophytes in nursing are strong obstacles to use of critical thinking skills in nursing. Rapid technological changes and increase consumer demand for health services dictate the need for professionally prepared nurses who are competent and capable of critical thinking abilities to process complex data and make and intelligent decision. But the question is, is nursing education and practice promoting critical thinking? This paper examines critical thinking in relation to other modes of thinking used by clinical nurses and issues in providing quality nursing care. In addition, thought processes that can influence nurse’s ability to provide safe, high-quality care are explored. The importance of exploring these thought process is to offer the reader a context in which to judge the appropriateness of nursing actions. Implications to nursing are discussed. Keywords: Critical thinking, nursing, disposition to critical thinking, evidence-based practice, uncertainty in nursing.